The efficacy of Aggression Replacement Training on interpersonal deficits and aggressive subtypes in New Zealand high school students : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate in Clinical Psychology at Massey University, Wellington, New Zealand - Mills, Jessica (Massey University, 2014)
Aggression Replacement Training (ART) is a three component intervention that targets the emotional, cognitive, and behavioural deficits associated with antisocial behaviour. Despite the growing number of outcome studies demonstrating the efficacy of ART in reducing antisocial behaviours, gaps in our understanding of how ART operates to create positive change remain. The current research aimed to reduce some of these gaps by trialling ART with three groups of high school students in New Zealand schools. Improvements in interpersonal competence that the intervention is claimed to target, empathy, and the proactive and reactive tendencies of aggression were investigated. This research also aimed to show the added value of the Moral Reasoning Training (MRT) component, over and above that of the Anger Control Training (ACT) and Social Skills Training (SST) components, by delivering the MRT component last and assessing change in variables over the course of the intervention. Overall the current research found multiple improvements from pre-test to follow-up, across a range of measures, consistent with theoretical expectations. Findings particularly suggest that ART may be a useful intervention for reducing reactive aggressive tendencies. However, little evidence was seen to suggest the ART is effective for reducing proactive aggression. This research also found changes across the course of the intervention that suggest the MRT component is a valuable addition to the overall intervention: particularly in reducing the cognitive distortions associated with overt antisocial behaviour, as well as increasing global stage moral reasoning. ART seems to be an acceptable intervention for students that warrants further investigation for use with students in New Zealand.
Keywords: Juvenile deliquents; Counselling; Aggressiveness in adolescence; Anger in adolescence; Behaviour therapy; Moral education; High school students; New Zealand; Aggression Replacement Training